Semantic accessibility effects of character semantic radicals in Chinese phonograms' recognition - Jiang, Meng; Cao, Ting; Tan, Ya; Duan, Jixiang; Qu, Daiyue (Frontiers in Language Sciences, 2025)
IntroductionPrior research concentrated on testifying to the presence of the semantic activation of semantic radicals as well as the separate role of a couple of modulating factors like Transparency of phonograms, Genuineness of phonograms, and Position of semantic radicals.MethodThe present study first proposed a hierarchy on the ease of semantic activation, namely, a hypothesis on the semantic accessibility of character semantic radicals in Chinese phonogram recognition, and empirically investigated the hypothesis. Specifically, the three modulating factors were manipulated in a lexical decision task.Results and discussionThe highest semantic accessibility was observed for the character semantic radicals seated in the high-frequency positions of opaque phonograms, followed by the character semantic radicals seated in the high-frequency positions of transparent phonograms, and the lowest semantic accessibility was observed for the character semantic radicals seated in the high-frequency or low-frequency positions of pseudo-phonograms. Results partially supported the hypothesis, suggesting that the semantic behavior of character semantic radicals was shaped by the host phonograms, which embodied the configuration of such modulating factors as phonograms' transparency, genuineness, and semantic radicals' position.